KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MEMBANGUN KARAKTER ISLAMI SISWA DI SDIT AL-MANAR CIBARUSAH - Zahrah Febrianti (MANTRA (Jurnal Manajemen Strategis), 2026)
This study aims to describe the implementation and effectiveness of the principal's transformational leadership in building Islamic character among students at SDIT Al-Manar Cibarusah. Using a descriptive qualitative method, data were collected from the principal and teachers through online interviews, observations, and documentation. The results of the study indicate that the principal's leadership style, characterized by uswah hasanah (exemplary behavior), inspirational motivation, and individual attention, is highly effective. This leadership has succeeded in fostering a religious school culture through integrated programs such as tahfiz and qira'ah, which have significantly improved the academic, social, and spiritual character of students.